STUDI KARAKTERISTIK PEMBAKARAN MINYAK PIROLISIS PLASTIK MENGGUNAKAN STEAM-ATOMIZING BURNER - Muhammad Sigit Cahyono; Ucik Ika Fenti Styana (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
One of the new and renewable energy resources is Plastic Pyrolysis Oil, that produced from pyrolysis process of plastic wastes. This oil could be utilized as energy source using steam-atomizing burner, which it burning characteristics dependent to air pressure that used in the burner. The objective of the research was to investigate the influence of air pressure on the burning characteristic of plastic pyrolysis oil using steam-atomizing burner. The raw material that used are dry LDPE wastes. First, it was heated in pyrolysis reactor using biomass combustion as energy source, produced pyrolsyis oil, noncondensable gases, and carbon black. The oil that produced is used as fuel for combustion in steam-atomizing burner, to know it burning characteristic, with variable air pressure on 1, 2, 3, 4, and 5 bar. The observation was made on fire temperature, the long of flame, and it efficiency, that showed by fuel consumption in burner and yield of plastic pyrolysis oil that produced. The experiment results showed that as the air pressure increased, all parameters were increased, that are fire temperature, the long of flame, fuel consumption in burner, and the yield of plastic pyrolysis oil that produced in the pyrolysis reactor.